2003
DOI: 10.1074/jbc.m300819200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Potentiates Amyloid-β Generation in Astrocytes and in Transgenic Mice

Abstract: Accumulation of the amyloid-␤ peptide (A␤) in the brain is crucial for development of Alzheimer's disease. Expression of transforming growth factor-␤1 (TGF-␤1), an immunosuppressive cytokine, has been correlated in vivo with A␤ accumulation in transgenic mice and recently with A␤ clearance by activated microglia. Here, we demonstrate that TGF-␤1 drives the production of A␤40/42 by astrocytes leading to A␤ production in TGF-␤1 transgenic mice. First, TGF-␤1 induces the overexpression of the amyloid precursor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 45 publications
2
119
0
1
Order By: Relevance
“…15 In parallel, we have previously demonstrated that TGF-b treatment in both murine and human cultured astrocytes leads to an increased transcription of APP and subsequent accumulation of Ab. 5 Although brain TGF-b levels are highly increased following cerebral ischemia, 29 TGF-b was reported to protect hippocampal, cerebellar and cortical 35 neurons receptors and through a recruitment of Smad3. 4 Here, we provide evidence that neurons lose both TGF-b signalling and PAI-1 expression with neuronal differentiation, a phenomenon associated to an overexpression of HtrA1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In parallel, we have previously demonstrated that TGF-b treatment in both murine and human cultured astrocytes leads to an increased transcription of APP and subsequent accumulation of Ab. 5 Although brain TGF-b levels are highly increased following cerebral ischemia, 29 TGF-b was reported to protect hippocampal, cerebellar and cortical 35 neurons receptors and through a recruitment of Smad3. 4 Here, we provide evidence that neurons lose both TGF-b signalling and PAI-1 expression with neuronal differentiation, a phenomenon associated to an overexpression of HtrA1.…”
Section: Discussionmentioning
confidence: 99%
“…5 TGF-b isoforms elicit their cell type-specific responses through the ligand-induced formation of a heteromeric receptor complex between the serine/threonine kinases TbR-I and TbR-II: the type II receptor binds TGF-b by its own, then recruits the type I receptor, allowing the transphosphorylation-mediated activation of TbR-I. The subsequent activation of the Smad (signalling mother against decapentaplegic peptide) transcription factor cascade thus regulates the transcription of key target genes.…”
mentioning
confidence: 99%
“…This is suggested by the presence of a TGF-␤1-responsive element in the APP promoter and TGF-␤1-stimulated release of endogenous A␤ 1-40/42 peptides by cultured human astrocytes. 47 Alternatively, TGF-␤1 production may be triggered by A␤, 48 or both peptides may be up-regulated concomitantly in neurons, glia, and vascular cells by acute ischemic events or chronic cerebrovascular insufficiency. 49,50 In A/T mice, A␤ and TGF-␤1 are overproduced from birth and throughout the lifespan, and it seems that their interaction is responsible for the progressive hemodynamic deficit of A/T animals.…”
Section: Ad-like Cerebrovascular Pathology In A/t Mice and Therapeutimentioning
confidence: 99%
“…With the development of P301L mouse models that develop neurofibrillary pathology, intense interest be- Increases vascular deposition, decreases plaque deposition [190][191][192] came focused on how A␤ would affect NFT formation. Injection of synthetic A␤ 42 into somatosensory cortex and contralateral hippocampus of P301L mice caused a fivefold increase in NFT numbers in the amygdala, which receives projections from both cortex and hippocampus.…”
Section: Tau-interacting Proteinsmentioning
confidence: 99%